Bauxite residue issues: II. options for residue utilization - Klauber, Craig; Gräfe, M.; Power, G. (Elsevier, 2011)
Worldwide bauxite residue disposal areas contain an estimated 2.7 billion tonnes of residue, increasing by approximately 120 million tonnes per annum. The question of what to do with bauxite residue arose with the development of the Bayer process for alumina refining and the recognition that it generated a large amount of waste material. In the subsequent 120 years, residues have been primarily disposed into long-term storage, with a wide range of industry practice depending on local circumstances. Ideally this residue would be utilized as an industrial by-product for other applications, leading to a zero waste situation. Despite over 50 years of research and hundreds of publications and patents on the subject, little evidence exists of any significant utilization of bauxite residue. In this review of public domain information the reasons are examined, future opportunities are identified, and a way forward is proposed. All avenues of residue "re-use" (or more appropriately "use") are considered, but emphasis is on the few highest volume uses of lowest risk. Utilization is defined as taking the residue in some non-hazardous form (as a by-product) from the alumina refinery site and then using it as feedstock for another distinct application. Although residues from different bauxites have generic similarities, their specific make-up and residue location can influence their suitability for a given type of use. There are four primary reasons for inaction on residue use: volume, performance, cost and risk, with the last two probably being paramount. In terms of cost there are better options for raw material input from virgin sources (lower cost for better grades) that do not come with the same perceived risks as bauxite residue. The risks are composition based (technical and community perception) and relate to: soda, alkalinity, heavy metals and low levels of naturally occurring radioactive material (NORM). Amongst the outcomes of this review are priority research recommendations to address the knowledge gaps identified that, amongst other factors, are impeding the implementation of residue use. This is the second in a series of four related reviews examining bauxite residue issues in detail. © 2011 Elsevier B.V. All rights reserved.